Spatial and temporal characteristics of drought in the Mu Us Sandy Land based on the Standardized Precipitation Index - Zhu, Yonghua; Li, Jiamin; Xi, Xiaokang; Zhang, Jie; Ma, Pengfei; Liang, Li’e; Luo, Pingping (Frontiers in Environmental Science, 2024)
Environment of Mu Us sandy land, northern Shaanxi, is fragile, revealing the temporal and spatial evolution of drought can provide reference for ecological construction and agricultural production. Based on the daily precipitation data of five meteorological stations from 1967 to 2020, the spatial and temporal evolution characteristics of drought in Mu Us sandy land of Northern Shaanxi were analyzed by using the methods of standardized precipitation index (SPI) and run length theory. The results show that: (1) the smaller the time scale, the higher the sensitivity of SPI to primary precipitation. (2) The annual, summer, autumn and winter SPI showed an upward and a wetting trend, and the fastest wetting speed in summer, while the spring showed an increasing trend of drought. (3) In the past 54 years, the duration, degree and intensity of drought events at SPI-3 and SPI-12 scales in the Mu Us Sandy Land of Northern Shaanxi showed insignificant decreasing trend, but the decreasing rate at SPI-12 scale was faster than that at SPI-3 scale. The intensity of agricultural drought is greater than that of hydrological drought in the Mu Us Sandy Land of Northern Shaanxi. The serious periods of agricultural drought and hydrological drought are November 2018 to May 2019 and April 1999 to July 2021, respectively.(4) Duration of drought events at two time scales in each region showed a decreasing trend. The longest durations of agricultural drought and hydrological drought were Yulin and Jingbian respectively; Shenmu and Dingbian are the regions with the fastest reduction rate of drought degree at the two scales respectively. Hengshan is the region with rapid reduction of drought intensity at the two scales, and also the region with large average drought intensity. It is the region with frequent occurrence of serious agricultural drought events and hydrological drought events.